Cyanobacterial blooms and water quality in two urban fish ponds (University Journal of Zoology, Rajshahi University, 2009)
The occurrence and abundance of cyanobacterial population was monitored monthly in two urban fish ponds in Rajshahi City Corporation area from January to December, 2006. The bloom was observed in March, August and September. Some environmental parameters such as water temperature, transparency, pH, Dissolved Oxygen(DO), free Carbon dioxide(CO2), Biological Oxygen Demand (BOD), NO2-N, NH3-N, NH4+, toxic ammonia, Oxidation reduction Index (rH2) were recorded and their relationship with the bloom formation by cyanobacteria are discussed. During the study period 23 species of cyanobacteria were identified. Among which Microcystis, Anabaena, Planktothrix were found to be the dominant genera. Microcystis aeruginosa was the most dominant species during the bloom period. At the peak bloom period, Microcystis aeruginosa comprised 81.64% and 83.24% of total cyanophyceae in pond-1 and pond-2, respectively. The initiation and persistence of natural bloom of cyanobacteria, especially Microcystis was found to be triggered by relatively high temperature (33.21-33.53°C), alkaline pH (8.8), and nutrient enrichment especially high NO2-N, NH3-N, and NH4+ concentration. Key words: Cyanobacterial bloom, nutrient, fish pond doi:10.3329/ujzru.v27i0.1960 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 79-84